2019
DOI: 10.1038/s41591-019-0358-x
|View full text |Cite
|
Sign up to set email alerts
|

IL1R1 is required for celastrol’s leptin-sensitization and antiobesity effects

Abstract: Celastrol, a pentacyclic triterpene is the most potent anti-obesity agent that has been reported to date 1. The mechanism of celastrol's leptin sensitizing and anti-obesity effects has not yet been elucidated. In this study, we identified interleukin 1 receptor 1 (IL1R1) as a mediator of celastrol action by using temporally-resolved analysis of the hypothalamic transcriptome in celastrol-treated DIO, lean and db/db mice. We demonstrate that IL1R1-deficient mice are completely resistant to celastrol's leptin se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 36 publications
3
82
0
1
Order By: Relevance
“…Intratumoral hypoxia upregulates the expression of VEGF, which can induce the angiogenesis in tumor . Sato A, et al also found that CoCl 2 -induced hypoxia treatment results in increased the secretion of VEGF in tumor cells (Feng et al, 2019). Once angiogenesis has been activated, tumors exhibit various forms of neovascularization which play a key role in promoting tumor growth, metastasis and invasion.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Intratumoral hypoxia upregulates the expression of VEGF, which can induce the angiogenesis in tumor . Sato A, et al also found that CoCl 2 -induced hypoxia treatment results in increased the secretion of VEGF in tumor cells (Feng et al, 2019). Once angiogenesis has been activated, tumors exhibit various forms of neovascularization which play a key role in promoting tumor growth, metastasis and invasion.…”
Section: Discussionmentioning
confidence: 96%
“…HUVECs migration assay was performed as described previously (Feng et al, 2019). Briefly, EA.hy 926 cells were allowed to grow to 90% confluence in gelatin-coated 6-well plates and then incubated with DMEM containing 0.5% FBS for 6 h to inactivate cell proliferation.…”
Section: Cell Migration Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Mice with advanced NASH ↓ ALT levels ↓ Hepatic steatosis ↓ Total hepatic cholesterol [ 100] QHD and GC Rats and mice fed with HFD ↓ Hepatic lipid synthesis ↓ Serum LPS level ↑ Gut barrier function [ 101] DCHD NASH rats fed a high-fat, high-fructose diet ↓ ALT and AST levels ↓ Liver coefficient ↓ Plasma endotoxin [ 102] Baicalin Mice fed with HFD ↓ Weight gain ↓ Hepatic steatosis ↓ Liver fat accumulation ↓ Hepatic TAG and cholesterol [ 103] Celastrol DIO and db/db mice ↓ Hepatic steatosis ↑ Insulin sensitivity ↓ ALT and AST levels [ 108] Ganoderma lucidum and its water extract HFD-fed mice ↓ Fat accumulation ↓ Liver inflammation ↓ Endotoxemia and IR [ 106] Micronutrient antioxidants -cryptoxanthin CL diet-fed mice ↓ Fat accumulation ↓ TBARS level ↓ Hepatic steatosis ↓ Liver inflammation ↓ IR and lipid peroxidation [ 109,110] Astaxanthin CL diet-fed mice ↓ Hepatic steatosis ↑ M2-dominat macrophages ↓ IR and liver inflammation ↓ Liver fibrosis [ 111] Liver samples from NAFLD patients ↓ Hepatic steatosis ↓ Total NAS score Lycopene HFD/CL diet-fed mice ↓ Lipid accumulation in liver ↓ Liver inflammation and IR ↑ M2-macrophage polarization [ 113,114] Vitamin D WD/VDD +/+ diet-fed rats ↑ Hepatic steatosis ↑ TLR4 activity ↑ NAS score [ 116] Vitamin E NASH patients ↓ ALT level ↓ NAS and fibrosis score [ 117] Polyphenols HepG2 cells ↓ ROS, TAG, and ALT ↓ Lipid peroxidation ↑ CAT, GPx, and SOD activities [ 118,165] MCD-fed NASH mice ↓ Hepatic steatosis ↓ ALT and AST level ↓ TBARS level [ 119] Probiotics…”
Section: Mastihamentioning
confidence: 99%
“…Screenings for novel leptin-sensitizing molecules using the bioinformatical Connectivity Map (CMAP) tool led to the identification of the plant constituents celastrol and withaferin A, which increase leptin sensitivity and reduce body weight of obese mice (93,94). The leptin-sensitizing properties of celastrol were later confirmed (95) and attributed to the hypothalamic inhibition of the protein tyrosine phosphatases PTP1B and TCPTP (96) and to an upregulation of the hypothalamic interleukin-1 receptor 1 (IL1R1) (97).…”
Section: The Journal Of Clinical Investigationmentioning
confidence: 99%